The Problem of Image’s Status: E. Alloa’s Symptomatology - Benediktas Vachninas (Problemos, 2023)
This article analyzes one of the most recent theories of visual thinking – Emmanuel Alloa’s symptomatology of images. The article focuses on the problem of the status of image, which is considered in various ways by authors of the pictorial and iconic turns. The article raises the question “What is the status of image in respect of language?” The article goes back to the origins of symptomatology of images, in particular, to Nelson Goodman’s theory of symbols. This allows showing the originality of Alloa’s model of symptoms and rehabilitating the status of symptomatological investigation. It is thus claimed that the iconic status of images in relation to language can be reformulated raising the question of the symptom’s identity. In this respect, the symptoms of iconic are instruments that enable the description of images with regard to different layers of iconicity.